SOWING SYSTEM AND AGRICULTURAL TECHNIQUES FOR GROWING NEWLY CREATED WHEAT VARIETIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
As a result of implementation of comprehensive measures in the field to meet the demand of the population of our republic for bread and bakery products at the expense of grain grown in our country, grain independence was achieved in a short period of time. Biologically, durum wheat differs from soft wheat in its resistance to drought, high temperature, yellow and brown rust and scab diseases, and does not spill when it is harvested. Therefore, in wheat breeding, it is important to pay special attention to the creation of soft and hard wheat varieties that are suitable for the conditions of each region, that is, resistant to the effects of various stress factors, with high yield and high grain quality.